Trinity Cathedral, Port of Spain. - (:unkn) unknown (My University, 2010)
Image depicts the Trinity Cathedral in Port of Spain Trinidad, in the Republic of Trinidad and Tobago. This is a view of the cathedral from the western corner of Hart Street, just inside the intersection with Abercromby Street. Almost all of the western end of the building is obscured by trees.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Cathedrals; Buildings